In-season resistance training and detraining in professional team handball players - Cardoso Marques, M. A.; Gonzalez-Badillo, J. J. (The Journal of Strength and Conditioning Research, 2006)
The object of this study was to investigate the changes in physical parameters produced during an in-season resistance training (RT) and detraining (DT, or RT cessation) in 16 high level team handball players (THPs). Apart from normal practice sessions, THPs underwent 12 weeks of RT. Subjects performed 3 sets of 3-6 reps with a load of 70-85% concentric 1 repetition maximum bench press (1RMBP), 3 sets of 3-6 reps with a load of 70-95% of 4 repetition maximum parallel squats (4RMPS), plus vertical jumps and sprints. The 1RMBP, 4RMPS, speed over 30 m (S30), jump (countermovement jump height [CMJ]; CMJ with additional weights [20kg and 40kg], and ball throw velocity (BTv) were tested before the experimental period (T1), after 6 weeks (T2), and after the 12-week experimental period (T3). Immediately after these 12 weeks, THPs started a 7-week DT period, maintained normal practices. The CMJ and the BTv were the only parameters evaluated during DT. The most important gains (p < 0.001) in S30 were obtained between T1-T2 and T1-T3. The BTv improved significantly (p < 0.001) only between T1-T2 and T1-T3. The most relevant increases (p < 0.001) in jumping performance took place between T1-T2 and T1-T3. The 1RMBP showed significant increases (p < 0.001) only between T1-T2 and T1-T3. The 4RMPS increased significantly between all testing trials. After the DT, THPs showed no significant losses in CMJ performance. However, they declined significantly in BTv (p = 0.023). The results suggest that elite THPs can optimize important physical parameters over 12 weeks in-season and that 7 weeks of DT, although insufficient to produce significant decreases in CMJ, are sufficient to induce significant decreases in BTv. It is concluded that after RT cessation THPs reduced BTv performance.